2006
DOI: 10.1007/s11434-006-2003-6
|View full text |Cite
|
Sign up to set email alerts
|

Variations of organic carbon isotopic composition and its environmental significance during the last glacial on western Chinese Loess Plateau

Abstract: A high-resolution loess section in the western Chinese Loess Plateau, Yuanbao Section, was sampled for organic carbon isotopic analyses. The soil organic carbon isotope (δ 13 C org ) varied between −22.6‰ and −27.5‰ during the last glacial at the section. During the last interstadial, the δ 13 C org values were more negative than those in both early and late periods of the last glacial by 4‰. The isotopic composition indicates a coupled response of the pure C 3 plants to the temperature, precipitation and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…When environmental temperature is below the "threshold value", especially during the growing seasons, C 4 plants will be absent in local ecosystem, such as the reconstructed paleovegetation in the high-latitudes since the Last Glacial [53,56,59] and that during the Last Glacial on the western edge of the CLP [35]. When environmental temperature is higher than the "threshold value", extremely arid, especially during the growing seasons, could also be adverse to the growth of C 4 plants, such as the modern vegetation in the Mediterranean climate zone (Pasadena in California and Seville in Spain [5] in Figure 1).…”
Section: Discussion On Driving Mechanisms and Its Significance 31 Drmentioning
confidence: 99%
See 3 more Smart Citations
“…When environmental temperature is below the "threshold value", especially during the growing seasons, C 4 plants will be absent in local ecosystem, such as the reconstructed paleovegetation in the high-latitudes since the Last Glacial [53,56,59] and that during the Last Glacial on the western edge of the CLP [35]. When environmental temperature is higher than the "threshold value", extremely arid, especially during the growing seasons, could also be adverse to the growth of C 4 plants, such as the modern vegetation in the Mediterranean climate zone (Pasadena in California and Seville in Spain [5] in Figure 1).…”
Section: Discussion On Driving Mechanisms and Its Significance 31 Drmentioning
confidence: 99%
“…Luochuan, Jiaodao, Jixian, Yanshi, Xunyi, Weinan, Lantian, Lingtai, Yuanbao, Xifeng, Huanxian, Baoji, Figure 1) on the Chinese Loess Plateau (CLP) [18,19,[33][34][35] show an increase of C 4 relative abundance from the Last Glacial to the Holocene. In the eastern and central CLP, the magnitude of C 4 increase in several profiles is ca.…”
Section: Global Paleo-c 3 /C 4 Records Since the Last Glacialmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past few decades, researchers have studied past vegetation and climate changes throughout different periods from sediments on the Chinese Loess Plateau with various methods, such as soil microstructure (Guo et al, 1993), sporopollen in loess deposits (Liu and Su, 1994;Sun et al, 1997;Wu et al, 2004;Long et al, 2011), phytoliths (Lv and Liu, 1999), and stable carbon isotopes (Ding and Yang, 2000;Gu et al, 2003;Zhang et al, 2003;Vidic and Montanez, 2004;Liu et al, 2005;Rao et al, 2006;Chen et al, 2006;Zhou et al, 2009Zhou et al, , 2014Yang et al, 2012). This previous research has generally found that grassland vegetation on the CLP was a mixture of C 3 and C 4 herbaceous plants, with a dominance of C 3 plants since late Quaternary, and at no previous time was the CLP dominantly forested (Gu et al, 2003;Zhang et al, 2003;Zhou et al, 2009;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%